His dark materials the complete collection - Thorne, Jack 1978-; Thorne, Jack 1978-; Keen Fernández, Daphne 2005-; Wilson, Ruth 1982- (BBC Studios, 2019)
"Based on author Philip Pullman's beloved trilogy, His dark materials season 1 follows Lyra, a brave young woman from another world. Lyra's quest to find her kidnapped friend leads her to uncover a sinister plot of a secret organisation, encounter extraordinary beings and protect dangerous secrets."
Bonus features: introducing His dark materials ; The Daemons: His dark materials ; Building His dark materials ; Dressing His dark materials ; Adapting His dark materials
Keywords: Film; DVD-Video